La ayuda económica norteamericana y los empresarios españoles - Puig, Núria (Cuadernos de Historia Contemporánea, 2003)
This article examines the effects of American economic aid on the modernization process of Spanish business and business people that took place under Franco’s dictatorship. The main idea is that American aid, in spite of its absolute and relative modesty, remained the most important foreign influence through the 1950s and contributed to articulate or strengthen outward looking and technologically advanced business groups and circles of various persuasions that have played a crucial role in the economic and institutional development of 20th century Spain.